(3GdJhLjg Gdafj hGdJQHhjs - (3GdafjT, CMeOs ((3HjQhJs (3OGQ GdcJGH GdLOjO GdeJMOIs, 2000)
(3cGfJ hXjaI GdeOQSI aj GdeGVj JYdje GdJdGejP GdbQGAI hGdcJGHI hGSJXgGQ GdebQQ GdOQGSj, CeG Gdjhe, aj Xd GdJMhdGJ GdLOjOI, CUHMJ hXjaI GdeOQSI JNQjL ehGWfjf ef YfOge ef GdcaGjI GdEfJGLjI eG jecfge ef GdJhGab eY GdeLJeY GdPj jYjThf ajg, hehGLgI eTcdGJg, hGdeTGQcI aj MjGJg eTGQcI PcqjI haqYGdI(B. (3Ef hXjaI GdeTQa Gdafj cbGFO JQHhj JJWdH bOQI Ydi age GdfGS hGdYed eYge cCaQGO hLeGYGJ, EfgG JJWdH GdbjGe HNOeGJ JYdjejI hGdbOQI Ydi EMOGK JZjjQ aj GdCTNGU haj GJLGgGJge hSdhcge(B. (3aj gPG GdEWGQ jCJj cJGH (B"(3GdJhLjg Gdafj hGdJQHhj(B" (3hGdPj jMGhd GdeDda ef NdGdg JbOje ELGHGJ Ydi LedI cHjQI ef GdCSFdI aj GdMbhd GdJQHhjI hGdafjI GdJj HGJJ JDQb cKjQkG ef GdHGMKjf aj gPG GdeLGd(B.s
(3GdfhY (B: (3cJGHs
Keywords: Orientation et Conseil; School guidance and counseling; (3GdJhLjg hGdEQTGO GdeOQSjs